A comparative study of clinical features of pleomorphic adenoma and malignant pleomorphic adenoma (carcinoma in pleomorphic adenoma) - TSUBAKIMOTO, Yuriko; YOSHIKAWA, Fumihiro; KATO, Itsuro; OHMAE, Masatoshi; IWAI, Souichi; SAKUDA, Masayoshi; Doi, Toshihide (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Pleomorphic adenoma is the most common tumor of the salivary gland. Usually, it grows slowly and has a good prognosis. However, some pleomorphic adenoma. generally referred to as malignant pleomorphic adenoma (carcinoma in pleomorphic adenoma) show invasive growth or distant metastasis. We examined clinical features in 69 patients who were given a diagnosis and treated at our clinic during the past 16 years. The 69 patients included 63 patients with pleomorphic adenoma and 6 patients with malignant pleomorphic adenoma. The 63 cases of pleomorphic adenoma occurred in 21 males and 42 females. The ratio of males to females was 1: 2, indicating a higher prevalence in females than males. The 6 cases of malignant pleomorphic adenoma occurred in 4 males and 2 females. The diagnosis was carcinoma in pleomorphic adenoma in 4 cases and so-calld malignant pleomorphic adenoma in the other 2 cases. Five of these patients were treated at our clinic; surgery was performed in all 5 patients. The 5 -year survial rate was 80%.